Medium-entropy alloy material, preparation method thereof, modified electrode containing medium-entropy alloy material, electrochemical sensor containing medium-entropy alloy material and application of medium-entropy alloy material

By modifying the electrodes with medium entropy alloy materials and building an electrochemical sensor, the problems of complex operation, high cost and time-consuming detection of nitrophenol in the prior art are solved, and a fast and sensitive detection effect is achieved.

CN119710421APending Publication Date: 2025-03-28HUIZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411716701.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The prior art is complex in the detection of nitrophenol, expensive in operation, and a long detection process, making it difficult to achieve fast and sensitive detection.

Method used

Medium entropy alloy material is used as electrode modification material, and medium entropy alloy material is prepared by vacuum smelting method, and modified on the surface of the substrate electrode to construct an electrochemical sensor to detect nitrophenol.

Benefits of technology

The rapid and sensitive detection of p-nitrophenol is achieved, with high sensitivity and low detection limits, and good stability is shown in the linear range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005157038350000131
    Figure BDA0005157038350000131
  • Figure BDA0005157038350000141
    Figure BDA0005157038350000141
  • Figure HDA0005157038360000011
    Figure HDA0005157038360000011
Patent Text Reader

Abstract

The invention particularly relates to a medium-entropy alloy material, a preparation method thereof, a modified electrode containing the medium-entropy alloy material, an electrochemical sensor containing the medium-entropy alloy material and application. The preparation method of the medium-entropy alloy material comprises the following steps that three metal elementary substance raw materials are mixed according to the molar ratio of 1: 1: 1, the mixture is placed in a vacuum smelting furnace to be smelted, and the medium-entropy alloy material is obtained; the three metal elementary substance raw materials are any three of Ni, Al, Mo, Fe, Cr, Al and Co. The modified electrode comprises a substrate electrode and the medium-entropy alloy material, and the medium-entropy alloy material is modified on the surface of the substrate electrode. The invention also provides application of the modified electrode in an electrochemical sensor and the electrochemical sensor containing the modified electrode. The medium-entropy alloy material shows good catalytic reduction activity on p-nitrophenol, and an electrochemical sensor constructed based on the medium-entropy alloy material is applied to detection of p-nitrophenol, so that a good analysis effect is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrochemical sensors, and specifically relates to a medium-entropy alloy material and a preparation method thereof, a modified electrode and an electrochemical sensor containing the same, and applications thereof. Background Art

[0002] As a common organic pollutant, p-nitrophenol is widely present in chemical wastewater, pesticide residues and various industrial emissions. The establishment and development of an analytical system for rapid response and sensitive detection of p-nitrophenol is of great significance for pollution prevention and control and source tracing. At present, the detection of p-nitrophenol mainly relies on a variety of technical means such as chromatography, optical method and electrochemical method. However, these traditional detection methods are often complicated to operate, the instrument cost is high, and the detection process is time-consuming. In contrast, the electrochemical method has the advantages of simple operation, low cost and fast analysis speed, and can achieve rapid and sensitive detection of p-nitrophenol concentration. In the design and construction of nitrophenol electrochemical sensors, the selection of electrode modification materials occupies a pivotal position. Suitable electrode modification materials can significantly improve the performance of the sensor, which plays a vital role in improving the sensitivity, selectivity and stability of nitrophenol detection.

[0003] In recent years, medium-entropy alloys, as an emerging material, have attracted widespread attention due to their unique physical and chemical properties, especially in the field of catalysis, showing great application potential. In the field of electrochemical catalysis, the application of medium-entropy alloys is increasing. Their unique electronic structure and surface characteristics give them excellent catalytic performance and can effectively promote the electrochemical reaction. When medium-entropy alloys are used as catalysts in electrochemical sensors, they can not only improve the response speed and sensitivity of the sensor, but also significantly enhance the overall performance of the sensor. In addition, medium-entropy alloys also play an important role in key areas such as energy conversion and storage, and degradation of environmental pollutants. For example, as an electrode material, medium-entropy alloys can improve the energy conversion efficiency of fuel cells, water electrolysis and other devices; as an additive to energy storage materials, it helps to improve the performance of batteries and other equipment; in terms of environmental purification, medium-entropy alloys can catalyze the degradation of harmful substances such as organic pollutants and heavy metal ions, making contributions to environmental protection.

[0004] In view of the many advantages of medium-entropy alloys in the field of electrochemical catalysis, the present invention aims to further explore their application in enzyme-free electrochemical sensors in order to further improve the performance of the sensors. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a medium-entropy alloy material and a preparation method thereof, a modified electrode and an electrochemical sensor containing the same and applications thereof. The medium-entropy alloy material of the present invention exhibits good catalytic reduction activity for p-nitrophenol. The electrochemical sensor constructed based on the medium-entropy alloy material of the present invention is applied to the detection of p-nitrophenol, and achieves good analytical results. It not only has high sensitivity and low detection limit, but also exhibits good stability within the linear range.

[0006] The technical solution adopted by the present invention to solve the above problems is as follows:

[0007] A method for preparing a medium-entropy alloy material comprises the following steps: mixing three metal single substance raw materials in a molar ratio of 1:1:1, placing the mixture in a vacuum melting furnace for melting, and obtaining the medium-entropy alloy material; the three metal single substance raw materials are any three of Ni, Al, Mo, Fe, Cr, Al, and Co.

[0008] Preferably, the smelting temperature is 1200° C. to 1400° C., and the smelting time is 15 min to 400 min.

[0009] More preferably, the smelting temperature is 1200° C. and the smelting time is 20 min.

[0010] Preferably, the method for preparing the medium-entropy alloy material further comprises: crushing and screening the medium-entropy alloy material to obtain a medium-entropy alloy material with a particle size of 0 to 25 μm.

[0011] A medium-entropy alloy material prepared by the above-mentioned method for preparing the medium-entropy alloy material.

[0012] A medium-entropy alloy modified electrode comprises a substrate electrode and the medium-entropy alloy material as described above, wherein the medium-entropy alloy material is modified on the surface of the substrate electrode.

[0013] Preferably, the substrate electrode includes but is not limited to a glassy carbon electrode, a platinum electrode or a diamond electrode. More preferably, the substrate electrode is a glassy carbon electrode.

[0014] Preferably, the medium-entropy alloy material is at least one of NiAlMo and FeCrAl.

[0015] A method for preparing the medium-entropy alloy modified electrode comprises the following steps: coating a mixed slurry comprising the medium-entropy alloy material and a binder on the surface of a base electrode, and obtaining the medium-entropy alloy modified electrode after drying.

[0016] Preferably, the particle size of the medium entropy alloy material is 0 to 25 μm.

[0017] Preferably, the binder is chitosan.

[0018] Preferably, the mass ratio of the medium-entropy alloy material to the binder is 100:1.

[0019] An application of the medium-entropy alloy modified electrode in an electrochemical sensor.

[0020] Preferably, in the application in an electrochemical sensor, the medium-entropy alloy modified electrode is used as a working electrode.

[0021] An electrochemical sensor comprises a counter electrode, a reference electrode, and the medium-entropy alloy modified electrode as the working electrode.

[0022] Preferably, the counter electrode includes but is not limited to a platinum wire or a carbon counter electrode.

[0023] Preferably, the reference electrode includes but is not limited to an Ag / AgCl electrode, a saturated calomel reference electrode or a hydrogen electrode.

[0024] More preferably, the electrochemical sensor comprises a platinum wire as a counter electrode, an Ag / AgCl electrode as a reference electrode, and the medium entropy alloy modified glassy carbon electrode as described above as a working electrode.

[0025] An application of the electrochemical sensor in detecting p-nitrophenol.

[0026] The present invention has the following beneficial effects:

[0027] (1) The present invention adopts a vacuum melting method to prepare medium-entropy alloy materials, ensuring that the gas impurity content during the melting process is extremely low, thereby ensuring the purity of the alloy and reducing the degree of oxidation; during the preparation process, the present invention selects a suitable alloy component ratio, melting temperature and time to ensure the uniformity of the resulting alloy composition and the stability of the phase structure, and successfully prepares a medium-entropy alloy material with stable performance and uniform structure.

[0028] (2) The medium-entropy alloy material prepared by the present invention is composed of a mixture of three metal elements in an equimolar ratio. The present invention achieves precise optimization of catalytic performance by finely regulating the element types, proportions and microstructures of the medium-entropy alloy; this optimization not only improves the catalytic efficiency of the medium-entropy alloy for specific reactions, but also enhances its stability and durability, so that it maintains stable catalytic performance during long-term use.

[0029] (3) The medium-entropy alloy material of the present invention exhibits good catalytic reduction activity for p-nitrophenol. The electrochemical sensor constructed based on the medium-entropy alloy material is applied to the detection of p-nitrophenol and achieves good analytical results. It not only has high sensitivity and low detection limit, but also exhibits good stability within the linear range. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The SEM images of the CrCoNi, NiAlMo, and FeCrAl medium-entropy alloy materials prepared in Preparation Examples 1-3 are shown;

[0031] Figure 2 XRD diagrams of CrCoNi, NiAlMo, and FeCrAl medium-entropy alloy materials prepared in Preparation Examples 1-3;

[0032] Figure 3 The AC impedance diagram of each of the entropy alloy modified electrodes in Examples 1-3;

[0033] Figure 4 The cyclic voltammetry curves of each of the entropy alloy modified electrodes in Examples 1-3 in a 0.1 mol / L KCl solution containing 5 mmol / L K3[Fe(CN)6];

[0034] Figure 5 Cyclic voltammetry curves of each medium entropy alloy modified electrode in Examples 1-3 in a 0.1 mol / L PBS solution (pH=6) containing 20 μmol / L p-nitrophenol;

[0035] Figure 6 Cyclic voltammetry curves of each medium entropy alloy modified electrode of Examples 1-3 in 0.1 mol / L PBS solution (pH=6) containing 20 μmol / L p-nitrophenol at different scan rates;

[0036] Figure 7 DPV curves of each medium entropy alloy modified electrode of Examples 1-3 in 0.1 mol / L PBS solution (pH=6) containing 20 μmol / L p-nitrophenol under different experimental conditions;

[0037] Figure 8 The DPV curves of each medium entropy alloy modified electrode of Examples 1-3 in a PBS solution containing 20 μmol / L p-nitrophenol at different pH values, and the relationship between the redox peak current and the pH value;

[0038] Fig. 9 The DPV curves of p-nitrophenol with different concentrations on the entropy alloy modified electrodes in Examples 1-3, and the relationship between the oxidation peak current and the p-nitrophenol concentration are shown. DETAILED DESCRIPTION

[0039] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments, and are not limitations of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] Unless otherwise specified, the test materials, reagents, methods and equipment used in the following examples are conventional test materials, reagents, methods and equipment in the technical field; unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources. The quantitative tests in the following examples were all repeated three times, and the data are the average or average ± standard deviation of the three repeated experiments.

[0041] Preparation Example 1: CrCoNi medium entropy alloy material

[0042] The three metal single substance raw materials of Cr, Co and Ni are mixed in a molar ratio of 1:1:1, and the mixture is placed in a vacuum melting furnace, and smelted at 1200°C for 20 minutes under vacuum conditions to obtain a CrCoNi medium-entropy alloy material. The obtained CrCoNi medium-entropy alloy material is crushed and sieved to obtain a CrCoNi medium-entropy alloy material with a particle size of 0 to 25 μm.

[0043] Preparation Example 2: NiAlMo medium entropy alloy material

[0044] Three metal single substance raw materials of Ni, Al and Mo are mixed in a molar ratio of 1:1:1, and the mixture is placed in a vacuum melting furnace, and smelted at 1200°C for 20 minutes under vacuum conditions to obtain a NiAlMo medium-entropy alloy material. The obtained NiAlMo medium-entropy alloy material is crushed and sieved to obtain a NiAlMo medium-entropy alloy material with a particle size of 0 to 25 μm.

[0045] Preparation Example 3: FeCrAl Medium Entropy Alloy Material

[0046] Three metal single substance raw materials of Fe, Cr and Al are mixed in a molar ratio of 1:1:1, and the mixture is placed in a vacuum melting furnace, and smelted at 1200°C for 20 minutes under vacuum conditions to obtain a FeCrAl medium-entropy alloy material. The obtained FeCrAl medium-entropy alloy material is crushed and sieved to obtain a FeCrAl medium-entropy alloy material with a particle size of 0 to 25 μm.

[0047] The CrCoNi, NiAlMo, and FeCrAl medium-entropy alloy materials prepared in Preparation Examples 1-3 were subjected to SEM and XRD tests.

[0048] The specific operation of SEM detection includes: using a HATACHI SU8010 scanning electron microscope to observe the morphological characteristics of CrCoNi, NiAlMo and FeCrAl samples. On a dry and clean SEM spotting table, paste conductive glue to ensure good conductivity and sample adhesion, use a toothpick to gently pick up a small amount of CrCoNi, NiAlMo and FeCrAl samples in turn, roll them evenly on the conductive glue, and use an ear-cleaning bulb to blow away the floating powder. After completing the sample preparation, the sample is gold-plated to enhance conductivity and image quality. Put the prepared spotting table into the SEM instrument, position the lens to the sample by precisely manipulating the lens position, adjust the focus and dispersion of the lens, and then adjust the magnification to obtain SEM images of different resolutions and observe the surface morphology of the sample.

[0049] The specific operation of XRD detection includes: Rigaku Ultimal V multifunctional X-ray powder diffractometer was selected for XRD test. A sufficient amount of sample was evenly spread over the entire sample slot and compacted tightly with a glass sheet to ensure the accuracy of the test results. Then, the excess sample on the edge of the glass groove was carefully removed to avoid interference with the experimental results. The prepared sample slot was then securely placed in the diffractometer. And all samples were uniformly set with precise scanning conditions: scanning range 5-80°, scanning speed 10° / min, to ensure the consistency of experimental conditions and comparability of data.

[0050] Figure 1 The SEM images of the CrCoNi, NiAlMo, and FeCrAl medium-entropy alloy materials prepared in Preparation Examples 1-3 are shown in Figure A. Figure A is a SEM image of the CrCoNi medium-entropy alloy material (a1: 2000 times, a2: 5000 times, a3: 15000 times); Figure B is a SEM image of the NiAlMo medium-entropy alloy material (b1: 2000 times, b2: 5000 times, b3: 10000 times); Figure C is a SEM image of the FeCrAl medium-entropy alloy material (c1: 2000 times, c2: 5000 times, c3: 15000 times).

[0051] Depend on Figure 1 It can be seen that the particles of CrCoNi, NiAlMo and FeCrAl medium-entropy alloy materials all have regular and nearly circular morphology. Among them, the surface of CrCoNi particles is relatively smooth, while the spherical surface of NiAlMo and FeCrAl particles is rough and porous. This rough porous structure has a larger specific surface area and abundant electrochemical active sites, which is expected to accelerate the electron transfer process in the electrode catalytic reaction and improve the electrocatalytic activity of the material.

[0052] Table 1 shows the particle sizes of the CrCoNi, NiAlMo, and FeCrAl medium-entropy alloy materials prepared in Preparation Examples 1-3.

[0053] Table 1:

[0054] Material D10 / μm D50 / μm D90 / μm CrCoNi 9.464 15.758 24.555 NiAlMo 7.863 14.721 24.821 FeCrAl 6.988 13.647 24.891

[0055] It can be seen from Table 1 that the size of the entropy alloy materials in CrCoNi, NiAlMo and FeCrAl is between 1 and 25 μm.

[0056] Table 2 shows the elemental analysis results of the CrCoNi, NiAlMo and FeCrAl medium entropy alloy materials prepared in Preparation Examples 1-3, unit: wt%.

[0057] Table 2:

[0058] Material Cr Co Ni Al Mo Fe C S O N CrCoNi 30.83 34.55 34.50 - - - 0.013 0.0016 0.036 0.003 NiAlMo - - Bal. 38.34 18.73 - 0.001 0.0036 0.039 <0.005 FeCrAl 32.18 - - 33.98 - 33.72 - - 0.038 -

[0059] It can be seen from Table 2 that the element analysis results of the CrCoNi, NiAlMo, and FeCrAl medium-entropy alloy materials are in line with the preset molar ratio, which confirms the effectiveness and success of the synthesis of CrCoNi, NiAlMo, and FeCrAl medium-entropy alloy materials.

[0060] Figure 2 These are the XRD diagrams of the CrCoNi, NiAlMo, and FeCrAl medium-entropy alloy materials prepared in Preparation Examples 1-3.

[0061] Among them, the XRD data of the CrCoNi medium entropy alloy material showed strong diffraction peaks at 44.216°, 51.522°, and 75.853° at 2θ, corresponding to the (111), (200), and (220) crystal planes similar to Co (JCPDS No.15-0806), respectively, with a Fm3m space group structure. The unit cell parameters show that α=β=γ=90°, the density of the alloy is calculated to be 8.788 g / cm 3 .

[0062] The XRD data of NiAlMo material show strong diffraction peaks at 41.186° and 44.141° at 2θ, which correspond to the (002) and (101) crystal planes similar to MnAl6 (JCPDS No.11-0416), respectively, and have a Ccmm space group structure. The unit cell parameters show that α=β=γ=90°, the density of the alloy is calculated to be 3.270 g / cm 3 .

[0063] The XRD data of FeCrAl medium entropy alloy material shows a strong diffraction peak at 42.611° at 2θ, which corresponds to the (330) crystal plane similar to Al8Cr5 (JCPDS No.29-0015) and has an R3m space group structure. The unit cell parameters show that α=β=γ=90°, the density of the alloy is calculated to be 4.264g / cm 3 .

[0064] The above results show that CrCoNi, NiAlMo and FeCrAl all have single crystal structures, which further confirms the successful preparation of medium-entropy alloy materials rather than a simple composite of metal elements.

[0065] The present invention adopts a vacuum melting method to prepare medium-entropy alloy materials, ensuring that the gas impurity content in the melting process is extremely low, thereby ensuring the purity of the alloy and reducing the degree of oxidation; in the preparation process, the present invention selects a suitable alloy component ratio, melting temperature and time to ensure the uniformity of the obtained alloy components and the stability of the phase structure, successfully prepares CrCoNi, NiAlMo, FeCrAl medium-entropy alloy materials with stable performance and uniform structure, and obtains ideal alloy properties.

[0066] Example 1: CrCoNi medium entropy alloy modified electrode

[0067] S1. Use 0.05μm Al2O3 polishing powder to add an appropriate amount of ultrapure water and mix evenly. Use the figure eight method to grind the surface of the glassy carbon electrode until the surface of the electrode becomes a bright mirror surface. Then rinse off the Al2O3 polishing powder on the surface of the glassy carbon electrode with deionized water and dry it to ensure the cleanliness of the electrode surface and form a smooth mirror surface.

[0068] S2. Disperse 30 mg of the CrCoNi medium-entropy alloy material obtained in Preparation Example 1 and 0.3 mg of chitosan into 1.5 mL of water until fully dispersed to obtain a uniform slurry. Use a pipette to evenly coat the mixed slurry on the surface of the glassy carbon electrode obtained in step S1, dry it at room temperature, and form a layer of stable modified material film on the surface of the glassy carbon electrode to obtain a CrCoNi medium-entropy alloy modified electrode.

[0069] S3. The CrCoNi medium-entropy alloy modified electrode prepared in Example 1 was used as the working electrode, a platinum wire was used as the counter electrode, and an Ag / AgCl electrode was used as the reference electrode to assemble a three-electrode test system, which was then connected to an electrochemical workstation for electrochemical performance testing.

[0070] Example 2: NiAlMo medium entropy alloy modified electrode

[0071] The preparation method of the medium-entropy alloy modified electrode is the same as that in Example 1, except that the CrCoNi medium-entropy alloy material prepared in Preparation Example 1 is replaced by the NiAlMo medium-entropy alloy material prepared in Preparation Example 2 to obtain a NiAlMo medium-entropy alloy modified electrode as a working electrode.

[0072] Example 3: FeCrAl medium entropy alloy modified electrode

[0073] The preparation method of the medium-entropy alloy modified electrode is the same as that in Example 1, except that the CrCoNi medium-entropy alloy material prepared in Preparation Example 1 is replaced by the FeCrAl medium-entropy alloy material prepared in Preparation Example 3 to obtain the FeCrAl medium-entropy alloy modified electrode as the working electrode.

[0074] In order to study the performance of the enzyme-free electrochemical sensor assembled with CrCoNi, NiAlMo and FeCrAl medium entropy alloy modified glassy carbon electrodes in Examples 1-3, all electrochemical analysis tests were completed based on the three-electrode system of the CHI 760E electrochemical workstation standard. That is, a bare glassy carbon electrode or a medium entropy alloy modified glassy carbon electrode was used as the working electrode, an Ag / AgCl electrode was used as the reference electrode, and a platinum wire was used as the counter electrode. The electrochemical analysis test process was completed at room temperature.

[0075] Test 1:

[0076] The impedance of the entropy alloy modified electrode in each example was studied in a 0.1 mol / L KCl solution containing 5 mmol / L K3[Fe(CN)6]; applied potential: open circuit voltage value; test frequency range: 100 KHz to 0.01 Hz; amplitude: 5 mV.

[0077] The results are as follows Figure 3 As shown in Table 3, Figure 3 1 is the AC impedance diagram of each medium entropy alloy modified electrode in Examples 1 to 3. Table 3 is the EIS fitting results of each medium entropy alloy modified electrode in Examples.

[0078] Table 3:

[0079] Modified Electrode Re(Ω) C(F) Rct(Ω) Warburg impedance error(%) CrCoNi 170.9 <![CDATA[4.185×10 -7 ]]> 943.0 <![CDATA[9.099×10 -4 ]]> 3.354 NiAlMo 136.6 <![CDATA[6.853×10 -9 ]]> 244.3 <![CDATA[1.773×10 -3 ]]> 4.060 FeCrAl 166.1 <![CDATA[5.591×10 -7 ]]> 222.6 <![CDATA[1.012×10 -3 ]]> 3.825

[0080] A typical EIS spectrum is presented as a combination of a semicircle in the high-frequency region and a straight line in the low-frequency region, where the intersection of the semicircle in the high-frequency region and the X-axis is the electrode-electrolyte contact resistance (Re); the diameter of the semicircle in the high-frequency region reflects the size of the Rct value; the Warburg impedance is a type of concentration polarization impedance, which is proportional to the electrolyte diffusion rate.

[0081] from Figure 3From the EIS results in Table 3, it can be seen that the modified electrodes of CrCoNi, NiAlMo, and FeCrAl medium-entropy alloys have similar Re; Rct(NiAlMo)≈Rct(NiAlMo)<<Rct(CrCoNi). This result reflects that the conductivity of the CrCoNi alloy is relatively weak, while NiAlMo and FeCrAl medium-entropy alloys have better conductivity; Warburg impedance (NiAlMo)>Warburg impedance (FeCrAl)>Warburg impedance (CrCoNi). This result indicates that the diffusion mass transfer rate of the modified electrodes is in the order of Warburg impedance (NiAlMo)>Warburg impedance (FeCrAl)>Warburg impedance (CrCoNi) from fast to slow. Based on the above results, compared with CrCoNi, NiAlMo and FeCrAl are more conducive to improving charge transfer kinetics, and thus are expected to show better electroanalytical performance in the determination of p-nitrophenol.

[0082] Test 2:

[0083] Cyclic voltammetry tests were carried out in a 0.1 mol / L KCl solution containing 5 mmol / L K3[Fe(CN)6], with the scanning potential range set at -0.1 V to 0.6 V and the scanning rate set at 50 mV / s.

[0084] The test results are as Figure 4 , Figure 4 are cyclic voltammograms of the modified electrodes of each medium-entropy alloy in Examples 1-3 in a 0.1 mol / L KCl solution containing 5 mmol / L K3[Fe(CN)6].

[0085] From Figure 4 it can be seen that the CV curve of the CrCoNi medium-entropy alloy modified electrode in a 0.1 mol / L KCl solution containing 5 mmol / L K3[Fe(CN)6] hardly shows an oxidation-reduction peak current, which is mainly due to its weak conductivity. In contrast, the FeCrAl medium-entropy alloy modified electrode and the NiAlMo medium-entropy alloy modified electrode show a pair of significant and maximum symmetric oxidation-reduction current peaks, fully demonstrating their excellent electron transfer ability. In summary, the FeCrAl medium-entropy alloy modified electrode shows the best conductivity and charge transfer ability improvement, while the CrCoNi medium-entropy alloy modified electrode shows relatively poor electrochemical performance.

[0086] Test 3:

[0087] Cyclic voltammetry was carried out in a 0.1 mol / L PBS solution (pH = 6) containing 20 μmol / L p-nitrophenol. The scanning potential range was set to -0.15 V to 0.3 V (CrCoNi medium-entropy alloy modified electrode), 0 V to 0.5 V (NiAlMo, FeCrAl medium-entropy alloy modified electrode), and the scanning speed was set to 50 mV / s.

[0088] Test results such as Figure 5 As shown, Figure 5 The cyclic voltammetry curves of the medium entropy alloy modified electrodes of Examples 1-3 in a 0.1 mol / L PBS solution (pH=6) containing 20 μmol / L p-nitrophenol are shown.

[0089] Depend on Figure 5 It can be seen that the redox current response signal of p-nitrophenol obtained on the CrCoNi medium-entropy alloy modified electrode is relatively weak. In contrast, the NiAlMo and FeCrAl medium-entropy alloy modified electrodes both obtained obvious redox peaks, which indicates that the NiAlMo medium-entropy alloy modified electrode and the FeCrAl medium-entropy alloy modified electrode have good catalytic activity for p-nitrophenol, while the catalytic performance of the CrCoNi medium-entropy alloy modified electrode is not as good as those of the NiAlMo medium-entropy alloy modified electrode and the FeCrAl medium-entropy alloy modified electrode.

[0090] Test 4:

[0091] The other conditions of test 3 remain unchanged, only the scanning speed is changed, and a cyclic voltammetry test is performed to measure the CV curves of each modified electrode in the example at different scanning speeds.

[0092] Test results such as Figure 6 As shown, Figure 6 The cyclic voltammograms of the medium entropy alloy modified electrodes in Examples 1-3 at different scan rates in 0.1 mol / L PBS solution (pH=6) containing 20 μmol / L p-nitrophenol are (a1) CrCoNi, (a2) NiAlM, (a3) ​​FeCrAl, and the relationship between the scan rate and the redox current are (b1) CrCoNi, (b2) NiAlMo, (b3) FeCrAl.

[0093] Depend on Figure 6 It can be seen that the redox peaks of the three medium-entropy alloy modified electrodes become more and more obvious with the increase of the scan rate. It can be seen that the electrochemical behavior of p-nitrophenol on the three medium-entropy alloy modified electrodes of CrCoNi, NiAlMo and FeCrAl shows typical diffusion control; and the diffusion control on the FeCrAl medium-entropy alloy modified electrode is stronger.

[0094] like Figure 6As shown in (b1), as the scanning rate increases to the 1 / 2 power (v 1 / 2 ) increases, the oxidation peak current (i pa ) and reduction peak current (i pc ) are significantly increased. Through data fitting, i pa and i pc With v 1 / 2 There is a linear relationship between them, specifically i pa =3×10 -7 v 1 / 2 -1×10 -6 , R 2 =0.9932; i pc =-3×10 -7 v 1 / 2 +1×10 -6 , R 2 =0.9928. The results show that the electrochemical behavior of p-nitrophenol on the CrCoNi medium entropy alloy modified electrode is typically diffusion controlled.

[0095] like Figure 6 As shown in (b2), we also observe that i pa and i pc Follow v 1 / 2 The data fitting also shows that i pa and i pc With v 1 / 2 There is a linear relationship between pa =1×10 -6 v 1 / 2 +4×10 -7 , R 2 =0.9994; i pc =-5×10 -7 v 1 / 2 -4×10 -6 , R 2 =0.9802. This result also shows that the electrochemical behavior of p-nitrophenol on the NiAlMo medium entropy alloy modified electrode is also controlled by diffusion.

[0096] like Figure 6 As shown in (b3), i pa and i pc Follow v 1 / 2 The increase of also shows the same trend. The fitting data result is i pa =8×10 -7 v 1 / 2 +2×10 -6 , R 2 =0.9994; i pc =-5×10 -7 v1 / 2 -3×10 -6 , R 2 =0.9916. The results show that the electrochemical behavior of p-nitrophenol on the FeCrAl medium entropy alloy modified electrode is also affected by diffusion control.

[0097] In summary, the electrochemical behaviors of p-nitrophenol on the three medium-entropy alloy modified electrodes all showed typical diffusion-controlled characteristics, which remained consistent at different scan rates.

[0098] Test 5:

[0099] In a 0.1 mol / L PBS solution (pH = 6) containing 20 μmol / L p-nitrophenol, the potential range was set to -0.15V~0.3V (CrCoNi medium-entropy alloy modified electrode) and 0V~0.5V (NiAlMo, FeCrAl medium-entropy alloy modified electrode); the three experimental conditions of potential increment (IncrE), amplitude (Amplitude) and pulse width (pulse width) were optimized respectively, and differential pulse voltammetry tests were carried out to explore the influence of different experimental conditions on the test performance.

[0100] The results are as follows Figure 7 As shown, Figure 7 The DPV curves of each medium entropy alloy modified electrode in Examples 1-3 in 0.1 mol / L PBS solution (pH=6) containing 20 μmol / L p-nitrophenol under different experimental conditions.

[0101] Figure 7 (a1), (a2) and (a3) ​​are DPV curves of CrCoNi medium entropy alloy modified electrode in 0.1 mol / L PBS solution (pH = 6) containing 20 μmol / L p-nitrophenol at different potential increments, amplitudes and pulse widths. It can be seen that when the potential increment (IncrE) is set to 20 mV / s, the amplitude (Amplitude) is 200 mV, and the pulse width (pulse width) is 20 ms, the test performance of the CrCoNi medium entropy alloy modified electrode is the best.

[0102] Figure 7 (b1), (b2) and (b3) are DPV curves of NiAlMo medium entropy alloy modified electrode in 0.1 mol / L PBS solution (pH=6) containing 20 μmol / L p-nitrophenol at different potential increments, amplitudes and pulse widths. It can be seen that the optimal potential increment (IncrE) of NiAlMo medium entropy alloy modified electrode is also 20 mV / s, the amplitude (Amplitude) is 200 mV, and the pulse width (pulse width) is also 20 ms.

[0103] Figure 7 (c1), (c2) and (c3) are the DPV curves of FeCrAl medium entropy alloy modified electrode in 0.1 mol / L PBS solution (pH=6) containing 20 μmol / L p-nitrophenol at different potential increments, amplitudes and pulse widths. It can be seen that the optimization parameters of FeCrAl medium entropy alloy modified electrode in differential pulse voltammetry (DPV) test are the same as those of the above two materials, that is, the optimal potential increment (IncrE) is 20 mV / s, the amplitude (Amplitude) is 200 mV, and the pulse width (pulse width) is 20 ms.

[0104] In summary, the optimal experimental conditions for CrCoNi, NiAlMo and FeCrAl medium-entropy alloy modified electrodes in differential pulse voltammetry (DPV) tests are: potential increment (IncrE) 20 mV / s, amplitude (Amplitude) 200 mV and pulse width (pulse width) 20 ms.

[0105] Test 6:

[0106] The DPV curves of each medium-entropy alloy modified electrode in Examples 1-3 in a PBS solution containing 20 μmol / L p-nitrophenol were measured at different pH values. The pH value of the solution was changed to perform differential pulse voltammetry tests, with the potential range set to -0.15 V to 0.3 V (CrCoNi medium-entropy alloy modified electrode) and 0 V to 0.5 V (NiAlMo, FeCrAl medium-entropy alloy modified electrode). The potential increment (IncrE) was set to 20 mV / s. The amplitude (Amplitude) was set to 200 mV. The pulse width (pulse width) was set to 20 ms.

[0107] The results are as follows Figure 8 As shown, Figure 8 The DPV curves of the medium entropy alloy modified electrodes of Examples 1-3 in PBS solution containing 20 μmol / L p-nitrophenol at different pH values ​​are (a1) CrCoNi, (a2) NiAlMo, (a3) ​​FeCrAl, and the relationship between the redox peak current and the pH value are (b1) CrCoNi, (b2) NiAlMo, (b3) FeCrAl.

[0108] Figure 8 It can be seen from (a1), (a2) and (a3) ​​that as the pH increases, the peak potential of the medium entropy alloy modified electrodes in Examples 1-3 will change. Figure 8It can be seen from (b1) that in a buffer solution with a pH value of 9, p-nitrophenol exhibits the best reduction current response on the CrCoNi medium entropy alloy modified electrode; Figure 8 It can be seen from (b2) that in the buffer solution with a pH value of 11, p-nitrophenol exhibits the best reduction current response on the NiAlMo medium entropy alloy modified electrode; Figure 8 It can be seen from (b3) that in a buffer solution with a pH value of 12, p-nitrophenol shows the best reduction current response on the FeCrAl medium entropy alloy modified electrode.

[0109] Test 7:

[0110] Differential pulse voltammetry test was carried out in a PBS solution containing 20 μmol / L p-nitrophenol, with the potential increment (IncrE) set to 20 mV / s, the amplitude (Amplitude) set to 200 mV, and the pulse width (pulse width) set to 20 ms; wherein the solution pH values ​​were 9 (CrCoNi medium-entropy alloy modified electrode), 11 (NiAlMo medium-entropy alloy modified electrode), and 12 (FeCrAl medium-entropy alloy modified electrode); the potential ranges were set to -0.15 V to 0.3 V (CrCoNi medium-entropy alloy modified electrode), and 0 V to 0.5 V (NiAlMo, FeCrAl medium-entropy alloy modified electrodes).

[0111] Test results such as Fig. 9 As shown, Fig. 9 DPV curves of different concentrations of p-nitrophenol on the entropy alloy modified electrodes in Examples 1-3 (a1) CrCoNi, (a2) NiAlMo, (a3) ​​FeCrAl; and the relationship between the oxidation peak current and the p-nitrophenol concentration (b1) CrCoNi, (b2) NiAlMo, (b3) FeCrAl.

[0112] like Fig. 9 As shown in (a1), with the gradual increase of p-nitrophenol concentration, the potential changes but no reduction peak appears; Fig. 9 (a2) and Fig. 9 As shown in (a3), the increase in p-nitrophenol concentration leads to a significant change in the DPV reduction current. The reduction current change of the FeCrAl medium entropy alloy modified electrode is higher than that of the NiAlMo medium entropy alloy modified electrode, so we believe that the electrochemical performance of the FeCrAl medium entropy alloy modified electrode is better than that of the NiAlMo medium entropy alloy modified electrode.

[0113] Fig. 9 (b1) shows the linear relationship of the redox current of the CrCoNi medium entropy alloy modified electrode in different p-nitrophenol concentration solutions, and its equation is ipc (A) = -2 × 10 -9 c-4×10 -7 , R 2 =0.8806, therefore, the detection range of p-nitrophenol on the CrCoNi medium entropy alloy modified electrode is 2.0~15.0μM, and the detection limit is 0.46μM.

[0114] Fig. 9 (b2) shows the linear relationship of the redox current of the NiAlMo medium entropy alloy modified electrode in different p-nitrophenol concentration solutions, and its equation i pc (A) = -9 × 10 -9 c-1×10 -6 , R 2 =0.9432, therefore, the detection range of p-nitrophenol on the NiAlMo medium entropy alloy modified electrode is 0.2~80.0μM, and the detection limit is 0.037μM.

[0115] Fig. 9 (b3) shows the linear relationship of the redox current of the FeCrAl medium entropy alloy modified electrode in different p-nitrophenol concentration solutions, and its equation is i pc (A) = -5 × 10 -8 c-1×10 -6 , R 2 =0.9877, therefore, the detection range of p-nitrophenol on the FeCrAl medium entropy alloy modified electrode is 2.0~60.0μM, and the detection limit is 0.36μM.

[0116] The analytical performance of electrodes modified with other materials for p-nitrophenol was further determined, and the results are shown in Table 4.

[0117] Table 4:

[0118]

[0119]

[0120] The preparation examples of the present invention successfully prepared three medium-entropy alloy materials, CrCoNi, NiAlMo and FeCrAl. The embodiments of the present invention successfully constructed an enzyme-free electrochemical sensor based on these three medium-entropy alloy materials. The present invention optimizes the manufacturing process and test conditions of the sensor, improves the sensitivity and response speed of p-nitrophenol detection, and can achieve quantitative detection of p-nitrophenol, showing better performance.

[0121] Comparing the performance of these three medium-entropy alloy materials in electrochemical sensors, it can be seen that the CrCoNi medium-entropy alloy material does not show significant catalytic activity and stability advantages in electrochemical sensors, while NiAlMo and FeCrAl medium-entropy alloy materials show good catalytic reduction activity for p-nitrophenol. The electrochemical sensors assembled based on NiAlMo and FeCrAl medium-entropy alloy materials are applied to the detection of p-nitrophenol and have achieved good analytical results. They not only have high sensitivity and low detection limit, but also show good stability within the linear range.

[0122] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0123] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0124] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A method for preparing a medium-entropy alloy material, characterized in that: The method comprises the following steps: mixing three metal single substance raw materials in a molar ratio of 1:1:1, placing the mixture in a vacuum melting furnace for melting, and obtaining a medium-entropy alloy material; the three metal single substance raw materials are any three of Ni, Al, Mo, Fe, Cr, Al, and Co.

2. The method for preparing a medium-entropy alloy material according to claim 1, characterized in that: The smelting temperature is 1200° C. to 1400° C., and the smelting time is 15 min to 400 min.

3. A medium entropy alloy material, characterized in that: Prepared by the preparation method of the medium-entropy alloy material according to claim 1 or 2.

4. A medium entropy alloy modified electrode, characterized in that: It comprises a substrate electrode and the medium-entropy alloy material as claimed in claim 3, wherein the medium-entropy alloy material is modified on the surface of the substrate electrode.

5. The medium-entropy alloy modified electrode according to claim 4, characterized in that: The medium entropy alloy material is at least one of NiAlMo and FeCrAl.

6. A method for preparing a medium-entropy alloy modified electrode according to claim 5, characterized in that: The method comprises the following steps: coating a mixed slurry comprising the medium-entropy alloy material and a binder on the surface of a base electrode, and obtaining the medium-entropy alloy modified electrode after drying.

7. Use of the medium-entropy alloy modified electrode according to any one of claims 3 to 6 in an electrochemical sensor.

8. The use of the medium entropy alloy modified electrode in an electrochemical sensor according to claim 7, characterized in that: The medium entropy alloy modified electrode is used as a working electrode.

9. An electrochemical sensor, comprising a counter electrode and a reference electrode, characterized in that: It also includes the medium-entropy alloy modified electrode described in any one of claims 3-6 as a working electrode.

10. Use of the electrochemical sensor according to claim 9 in detecting p-nitrophenol.